Influence of natural polymer derived from starch as a sensory modifier in sunscreen formulations - Rigon, Roberta B. [UNESP]; Piffer, Adrielle R.; Lima, Aline A. S.; Bighetti, Aparecida E.; Chorilli, Marlus [UNESP] (My University, 2013)
Background: Nowadays, there has been increased incidence of skin cancer, which is mainly related to increased sun exposure. Although sunscreen products may prevent the appearing of this disease, consumers may not use them due to some factors, including the sensory properties. The Aluminum Starch Octenylsuccinate (Dry-Flo® Pure, Akzo Nobel), an aluminum salt produced by the reaction of anhydride octenylsuccinic with starch, is able to improve the spreadability on the skin and reduce the oiliness of the formulation. Objective: To verify volunteers' acceptance for sunscreen formulation with natural polymer, compared with a control formulation (without polymer). Methods: To carry out the sensory analysis a formulation with or without 2. 0% Aluminum Starch Octenylsuccinate was prepared. Formulations had FPS 15, with critical wavelength of 353 nm, determined by testing in silico using the BASF® Sunscreen Simulator. Sensory analysis was performed on 60 students of both sexes, aged between 18 and 25 years, regular users of sunscreen products. Results: The results suggested that the polymer was able to promote a very soft and velvety feel on the skin when used in a sunscreen formulation, and it was able to mitigate and noticeably reduce the oiliness of the skin. Of the 60 volunteers who participated in the study, 45 volunteers (75%) considered that the polymer formulation provides little brightness or did not notice the difference in brightness of the skin after application. Conclusions: It was able to improve the sensory of the product, contributing to greater volunteers' acceptance.
Keywords: Aluminum starch octenylsuccinate; Sensory analysis; Sensory modifier; Sunscreen; aluminum salt; aluminum starch octenylsuccinate; basf; polymer; starch; sunscreen; unclassified drug; adult; brightness; comparative study; consumer; controlled study; female; human; human experiment; male; oily skin; questionnaire; sensory analysis; skin absorption; skin cancer; sun exposure; volunteer